Reconstruction of the upper region of the back with a V-Y trapezius musculocutaneous flap based on the dorsal artery of the scapula - João Lorenzo Bidart Sampaio Rocha; Geruza Rezende Paiva; Lorenzo Carvalho Sampaio Rocha; Allan Gomes Queiroga; Felipe Gomes Queiroga (Revista Brasileira de Cirurgia Plástica, 2024)
Introduction: Defects in the upper region of the back are generally difficult to treat, especially in cases of exposure of vertebrae, meninges, or synthetic material. Primary closure with a muscular or musculocutaneous flap is the best choice, but the donor area to treat large defects may require grafting. Preservation of the dorsal artery of the scapula appears to ensure a larger cutaneous territory than that of the classic trapezius musculocutaneous flap based only on the transverse cervical artery. Method: A wide triangular island of skin was designed over the trapezius muscle based on the dorsal scapular artery with pendulum transfer and a V-Y type procedure in five patients after the extirpation of malignant tumors. Results: The defects and donor areas were closed primarily with full viability of the flaps and no complications were observed other than the occurrence of seroma. Conclusion: The trapezius musculocutaneous flap based on the dorsal artery of the scapula offers safety in the treatment of bone exposure in the upper back region.